Multiphase graphitisation of carbon xerogels and its dependence on their pore size. (November 2019) - Canal-Rodríguez, María; Ramírez-Montoya, Luis A.; Villanueva, Sara F.; Flores-López, Samantha L.; Angel Menéndez, J.; Arenillas, Ana; Montes-Morán, Miguel A.
Abstract: Six carbon materials were obtained from the carbonisation of resorcinol/formaldehyde xerogels. All carbon xerogels (CXs) showed essentially the same microporosity but differed in their meso- or macroporosity, covering a wide interval of average meso- or macropore sizes from 10 nm to 3000 nm. The graphitisation of the CXs was heterogeneous, as detected by X-ray diffraction. The relative amount of the amorphous, turbostratic and graphitic carbon phases on the graphitised xerogels was different depending on the pore size of the CXs. Crystalline parameters such as interlayer spacings (d002 ) and crystallite sizes along the c-axis (Lc ) were calculated from the different contributions and were also found to depend on the pore size of the parent CXs. Transmission electron microscopy and Raman spectroscopy analyses helped to identify nanostructures that could be assigned to the three carbon components of the graphitic xerogels. The occurrence of most of these nanostructures was compatible with a solid-phase transformation of the amorphous precursor. The electrical conductivity of the graphitised xerogels also depended on their original pore size, with values ranging from 2 S cm −1 for the materials with a 10 nm pore size to 18 S cm −1 for the materials with bigger pore sizes. Graphical abstract: Image 1